High gelatinous salted duck egg white protein powder gel: Physicochemical, microstructure and techno-functional properties - Yao, Xinjun; Xu, Jicheng; Xun, Yu; Du, Tianyin; Huang, Mengqi; Guo, Jun (Frontiers in Nutrition, 2023)
Salted duck egg is one of the most popular products, and China is one of the major countries consuming salted duck egg products. However, due to the high salt content of salted egg white and low physical and chemical properties such as gel, many factories generally only use salted egg yolk and discard salted duck egg white (SDEW) as a waste liquid when processing. This is not only a waste of resources, but also a pollution to the environment. In this paper, protein powder was prepared from salted egg white. Then xanthan gum (XG) was added to make it co-gel with ovalbumin to achieve the purpose of preparing high gelatinous salted egg white protein powder. The results showed that the optimum conditions of SDEW-XG composite gel were as follows: the xanthan gum content was 0.08g, the reaction pH was 6.5, and the heating temperature was 100℃. Under these conditions, the gel strength reaches the maximum value. Meanwhile, compared with the protein powder without xanthan gum, the addition of xanthan gum significantly affected the secondary structure of the protein powder of SDEW and improved the water holding capacity of the gel. In conclusion, the addition of xanthan gum can significantly improve the gel quality of SDEW protein powder, which provides a theoretical basis for the quality improvement of salted egg white.